Digital Literacy, Online Reading Strategies, and Reading Comprehension of Efl Junior High School Students in Google Classroom: A Qualitative Study - Salsabila Salsabila; Asbar Asbar; Mustakim Mustakim (Universitas Cokroaminoto Palopo, 2026)
Prior research has largely assumed that exposure to digital environments naturally promotes critical literacy, yet empirical evidence from junior high school students in low-exposure, policy-constrained contexts remains scarce. This study therefore aims to explore the digital literacy practices and online reading strategies of EFL eighth-grade students when reading English texts through Google Classroom at SMP Negeri 2 Enrekang, a school enforcing a strict no-smartphone policy, in order to understand how institutional constraints shape students’ digital reading engagement. Employing a descriptive qualitative design grounded in the interpretivist paradigm, eight students were selected through purposive sampling. Data were collected via semi-structured interviews, open-ended questionnaires, classroom observation, a reading comprehension task, and documentation, then analyzed using Miles, Huberman, and Saldaña’s (2014) interactive model. Findings reveal that students’ digital literacy remained operational rather than critical, dominated by smartphone-based access, navigation difficulties, and heavy reliance on Google Translate. Online reading strategies were surface-level (skimming, scanning, translation-assisted rereading), while higher-order strategies particularly evaluating were rarely or never observed across any data source. Three reader profiles emerged: the Assisted Decoder, the Task-Oriented Navigator, and the Emerging Strategist. The study concludes that three converging constraints linguistic limitation, institutional device restriction, and instructional absence collectively explain students’ critically underdeveloped digital reading, calling for explicit strategy-focused pedagogy embedded in everyday instruction.